System and analytical research of the development of transport and technological systems of railway ferries - Kazymyrenko, Yuliia; Drozd, Oxana; Yeholnikov, Oleander; Morozova, Hanna (Technology audit and production reserves, 2020)
The object of research is the development processes of transport and technological systems of railway ferries as complex technical systems. In the course of the study, a systematic approach to solving the scientific and technical problem of increasing the efficiency of maintenance of railway ferry services is used, for which a graphical method is used to analyze the formation of cause and effect ties with the construction of Ishikawa diagrams. According to the most informational criterion, the reserve for accelerating the speed of railcars on railway ferries is selected – a qualitative characteristic of the efficient use of the railway fleet, which directly depends on the reduction of railway outages in the port area, is promising. The research results provide a multifaceted picture that shows the possibility of reducing the time spent on the ship at the port by increasing the technical level of organizational work with rolling stock on access roads and loading them on a ferry. It also affects the state of the material and technical base for servicing rolling stock and the port base for loading ferries, the compatibility of operations of dispatch services and the need for appropriate information support. However, the development of these areas is impossible without ensuring conditions for the reliability of railway automation, automation and telemechanics, as well as advanced training of personnel for their maintenance. The compatibility of operations of dispatch services is implemented through the use of flexible forms of organization of cargo flows with the preparation of an optimal cargo plan for loading a railway ferry. The implementation of information support should take into account the synchronization of the information systems of the railway and port, as well as the relationship of automation with the work of the ferry, constantly updated with new software products. Based on the analysis, a program of measures has been drawn up for the development of transport and technological systems of railway ferries. The obtained results are aimed at increasing the efficiency, validity and effectiveness of management work on the operation of means of transport and can be used in carrying out research work of other objects of railway-water communication, in particular port railways.